An Archaeal Chitinase With a Secondary Capacity for Catalyzing Cellulose and Its Biotechnological Applications in Shell and Straw Degradation - Chen, Lina; Wei, Yi; Shi, Mao; Li, Zhengqun; Zhang, Shi-Hong (Frontiers in Microbiology, 2019)
Numerous thermostable enzymes have been reported from the hyperthermophilic archaeon Thermococcus kodakarensis KOD1, which made it an attractive resource for gene cloning. This research reported a Glycosyl Hydrolase (Tk-ChiA) form T. Kodakarensis with dual hydrolytic activity due to the presence of three binding domains with affinity towards chitin and cellulose. The Tk-ChiA gene was cloned and expressed on Pichia pastoris GS115. The molecular weight of the purified Tk-ChiA is about 130.0 kDa. By using Chitosan, CMC-Na and other polysaccharides as substrates, we confirmed that Tk-ChiA with dual hydrolysis activity preferably hydrolyzes both chitosan and CMC-Na. Purified Tk-ChiA showed maximal activity for hydrolyzing CMC-Na at temperature 65°C and pH 7.0. It showed thermal stability on incubation for 4 h at temperatures ranging from 70 to 80°C and remained more than 40% of its maximum activity after pre-incubation at 100 °C for 4 h. Particularly, Tk-ChiA is capable of degrading shrimp shell and rice straw through Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR) analysis. The main factors affecting shell and straw degradation were determined to be reaction time and temperature; and both factors were optimized by central composite design (CCD) of response surface methodology (RSM) to enhance the efficiency of degradation. Our findings suggest that Tk-ChiA with dual thermostable hydrolytic activities maybe a promising hydrolase for shell and straw waste treatment, conversion and utilization.